Amphetamine‐related intoxications in people living with HIV: An observational study in an emergency department in Barcelona (Spain) from 2018 to 2020. Issue 3 (9th August 2022) - Perello, Rafael; Losada, Aelajandra; Chen Qin, Jiwei; Supervia, August; Salgado, Emilio; Smithson, Alex; Xipell, Marc; Inciarte, Alexis; Vallecillo, Gabriel
Abstract: Background: Stimulant drugs, particularly amphetamines, are more commonly implicated in drug‐related deaths in people living with HIV; however, the clinical characteristics of amphetamine‐related intoxication in people living with HIV are poorly described. Material and methods: We conducted a retrospective study in people living with HIV who were admitted for amphetamine‐related intoxication to an emergency department of a teaching hospital between 2018 and 2021. Severe intoxication (SI) was arbitrarily defined as requiring admission to the emergency medical support unit and receiving medical treatment for ≥6 h. Results: In total, 170 male patients with a median age of 36.2 + 7.5 years were included in the study. A total of 77 (45.3%) individuals had mental disorders, and 120 (85.7%) had HIV‐1 RNA suppression, with a median CD4 cell count of 696 (interquartile range 490–905). In total, 61 (37.9%) individuals were on ritonavir/cobicistat‐based regimens. Presenting clinical syndromes included agitation in 60 (35.3%) subjects, anxiety in 37 (21.7%), psychosis in 27 (15.8%), chest pain in 26 (15.3%) and altered level of consciousness in 20 (11.7%). SI was observed in 48 (28.2%) individuals, 12 (7.1%) required admission to the intensive care unit, and two (1.2%) died. Altered level of consciousness (odds ratio [OR] 6.5; 95% confidence interval [CI] 2.2–18.9; p < 0.01), psychosis (OR 5.8; 95% CI 2.2–15.1; p < 0.01) and suicide attempt (OR 4.6; 95% CI 1.8–11.6; p 0.01) were associated with SI in the adjusted analysis. Conclusions: Amphetamine‐related intoxication causes high morbidity in people living with HIV. Healthcare providers serving these patients should consider incorporating harm‐reduction measures in the prevention of amphetamine‐related intoxication.